Ignition of porous high-energy substances by light radiation; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 4 : Power engineering - Subbotin A. N. Aleksandr Nikolaevich (Power engineering, 2007)
Заглавие с титульного листа